Changes in Astigmatism Before and After Pterygium Surgery - Parajuli, Rojeeta; Bajracharya, Leena (Birat Journal of Health Sciences, 2019)
Introduction: Pterygium is a degenerative condition of the subconjuctival tissue, which proliferates as vascularised granulation tissue to invade the cornea resulting in destruction of the superficial layer of the corneal stroma and bowman's membrane. This change in cornea leads to corneal opacity, visual impairment and significant induced astigmatism. The ensuing pathologic changes consist of elastoid degeneration of collagen and the appearance of subepithelial fibrovascular tissueObjective: To measure the change in corneal astigmatism after pterygium surgery and the relationship of astigmatism with respect to size of pterygium.Methodology: Hospital based prospective, non-randomized study, comprising 61 eyes of 56 patients who underwent pterygium excision and autologus conjuctival graft during the period October 2009 to September 2010. A total of 56 participants were enrolled and followed upto 3 months after surgery. Corneal topography was used to measure corneal astigmatism before and after pterygium surgery.Results: The mean age of patient was 46.11 years, standard deviation was 18.86 Male: female ratio: 0.8:1 Preexisting induced astigmatism among study group patients was 2.6D and mean astigmatism after pterygium surgery was 0.8D. This finding was found to be statistically significant(P value